The Transformation of the Refund Provisions of Tabarru' in Islamic Insurance: Fatwa DSN-MUI No. 53/2006 and No. 81/2011 - Fitriansyah, Helmi; Rukmini, Neng Vivie Nurfauziah; Al Hakim, Sofian (Al-Muamalat: Jurnal Ekonomi Syariah, 2025)
This article examines the management of Tabarru' funds in Islamic insurance by analyzing DSN-MUI Fatwa No. 53/2006 and No. 81/2011, which play a crucial role in addressing operational and legal challenges within the Islamic insurance industry. The background of this study focuses on legal uncertainties concerning the status of Tabarru' funds as non-refundable grants, as stipulated in Fatwa No. 53/2006. In contrast, Fatwa No. 81/2011 introduces flexibility by allowing partial refunds for participants who terminate their contracts early, adapting to market needs. The regulatory changes introduced by Fatwa No. 81/2011 permit the partial refund of Tabarru' funds for participants who terminate their contracts before the agreed period concludes. This study employs a normative juridical approach, involving a comprehensive analysis of primary and secondary legal texts, including DSN-MUI fatwas, Islamic legal literature, and case studies on the implementation of these fatwas in the practice of Islamic insurance in Indonesia. Data are collected through library research and analyzed descriptively and comparatively to understand the roles of both fatwas in the management of Tabarru' funds and their implications. The findings indicate that Fatwa No. 81/2011 significantly contributes to the management of Tabarru' funds by introducing flexibility in refunding participants. The fatwas concerning Tabarru' funds in Islamic insurance demonstrate that they complement each other in regulating the concept and management of these funds. The operational implications of this study include recommendations to strengthen regulations and transparency in the management of Tabarru' funds and to enhance the protection of participants' rights.